2016
DOI: 10.1136/thoraxjnl-2016-208660
|View full text |Cite
|
Sign up to set email alerts
|

The obstructive sleep apnoea syndrome in adolescents

Abstract: OSAS in adolescents is mediated by a combination of anatomic (ATV, NPAV) and neuromotor factors (activated Pcrit). This may have important implications for the management of OSAS in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…This is in keeping with literature demonstrating that obesity-related OSA is multifactorial—that is, related to lymphoid hyperplasia, increased fat deposition in the upper airway, and neuromotor factors predisposing to upper airway collapsibility. 24,25 Specifically, in a recent static magnetic resonance imaging study, Schwab and colleagues demonstrated the importance of adenoid and tonsillar hypertrophy in the pathogenesis of OSA in obese adolescents. 25 Our study is in agreement with these results and provides clinicians with a potential easy-to-use predictive tool for screening the obese pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…This is in keeping with literature demonstrating that obesity-related OSA is multifactorial—that is, related to lymphoid hyperplasia, increased fat deposition in the upper airway, and neuromotor factors predisposing to upper airway collapsibility. 24,25 Specifically, in a recent static magnetic resonance imaging study, Schwab and colleagues demonstrated the importance of adenoid and tonsillar hypertrophy in the pathogenesis of OSA in obese adolescents. 25 Our study is in agreement with these results and provides clinicians with a potential easy-to-use predictive tool for screening the obese pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming increasingly recognized that in adolescents and adults, the pathophysiology of SDB is a complex interaction between an anatomically compromised airway and other non-anatomical factors or traits. 15,16 A number of non-anatomical traits have been identified in the adult literature, including neuromuscular activation of the pharyngeal dilators, the respiratory arousal threshold and ventilatory control stability, as contributors to the development of OSA. 8 Despite the increased understanding of these non-anatomical traits, characterising these traits in individual patients has proved difficult as they require specialised, invasive techniques.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that children and adolescents, with or without obesity, have less upper airway collapsibility compared to adult population. [49][50][51][52] This could explain that OSA is seen more commonly Adult patients herein had lower quality of life than narcoleptic children. As previously reported, narcoleptic patients experience difficulties in social relationships, whether in childhood or adulthood.…”
Section: Discussionmentioning
confidence: 95%
“…Although less obese, adult patients had more OSA than children. It has been shown that children and adolescents, with or without obesity, have less upper airway collapsibility compared to adult population 49‐52 . This could explain that OSA is seen more commonly among older people for the same degree of obesity.…”
Section: Discussionmentioning
confidence: 99%